PENGARUH FRAKSI VOLUME DAN ARAH SERAT RAMI TERHADAP KEKUATAN IMPAK MATERIAL KOMPOSIT UNTUK APLIKASI BUMPER - Astuti, Fina Andika Frida; Arif Rochman Fachrudin; Mira Esculenta Martawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid growth of the automotive industry demands ongoing innovation in material engineering to improve vehicle performance and safety. The bumper, as a key structural component, must provide collision protection while supporting fuel efficiency and reducing environmental impact. A major challenge is producing bumpers that are both strong and lightweight, prompting exploration of composite materials. Among natural fibers suitable for composite reinforcement, ramie fiber is a promising candidate. Ramie fiber offers several advantages, including high mechanical strength and relatively low density. The objective of this study is to develop a composite material with high impact strength as an alternative bumper material. An experimental research method was employed, with composite fabrication carried out using the hand lay-up technique. The variables in this study included fiber orientation vertical, horizontal, and random. Volume fraction with variations of 30% fiber and 70% matrix; 45% fiber and 55% matrix; and 60% fiber and 40% matrix. The results indicate that both fiber orientation and volume fraction significantly affect impact strength. The lowest impact strength was observed in specimens with horizontal fiber orientation and a 30% fiber volume fraction, yielding 0.00719 J/mm². The highest impact strength was obtained from specimens with vertical fiber orientation and a 60% fiber volume fraction, reaching 0.05578 J/mm². Based on these findings, ramie fiber composites meeting the minimum impact strength standard for Toyota bumpers are those with a 60% fiber and 40% matrix composition, particularly with random or vertical fiber orientations.